THE EFFECT OF INCOME AND MOTIVATION ON THE PERFORMANCE OF HARVESTERS AT MARPINGGAN PALM OIL PLANTATION PTPN IV AFDELING V - Rendi Syaputra Sihombing; Eka Bobby Febrianto (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to analyze the effect of income and motivation on the performance of harvesters at the Marpinggan Palm Oil Plantation PTPN IV Afdeling V. The research was conducted from January to June 2026 with 27 harvester respondents selected using the census method. The data was analyzed using multiple linear regression with the help of SPSS version 23. The research results show that income and motivation have a positive and significant effect on harvester performance. The regression equation obtained is Y = 8.857 + 0.383X₁ + 0.427X₂. The coefficient of determination (R²) value of 0.427 shows that 42.7% of the variation in harvester performance can be explained by income and motivation, while 57.3% is influenced by other factors outside the study. Motivation is the most dominant variable affecting harvester performance.